Analysis of the Financial Performance of the Regional Development Planning Agency (Bappeda) of North Sumatra Province - Sahnila Sikumbang; Marliyah Marliyah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The North Sumatra Province Regional Development Planning Agency (BAPPEDA) of North Sumatra Province is a regional technical institution in the field of regional development planning led by a head of agency who is under and responsible to the Governor/Regent/Mayor through the regional secretariat. This study aims to assess the financial performance of Bappeda North Sumatra Province for five fiscal years. In measuring financial performance, this is more focused on the Budget Realization Report (LRA). This financial performance measurement is carried out to determine the absorption of the budget and the use of the budget carried out for five budget years in the activities that exist in the agency itself. This research uses a qualitative approach with data collection techniques in the form of documentation.